Effects of Mesenchymal Stromal Cell-Derived Extracellular Vesicles on Tumor Growth - Bruno, Stefania; Collino, Federica; Iavello, Alessandra; Camussi, Giovanni (Frontiers in Immunology, 2014)
Extracellular vesicles (EVs) are membrane vesicles, which are secreted by a variety of cells that have a relevant role in intercellular communication. EVs derived from various cell types exert different effects on target cells. Mesenchymal stromal cells (MSCs) are stem cells that are ubiquitously present in different tissues of the human body, and MSC-derived EVs take part in a wide range of biological processes. Of particular relevance is the effect of MSCs on tumor growth and progression. MSCs have opposing effects on tumor growth, being able either to favor angiogenesis and tumor initiation, or to inhibit progression of established tumors, according to the conditions. Different studies have reported that EVs from MSCs may exert either an anti- or a pro-tumor growth effect depending on tumor type and stage of development. In this review, we will discuss the data presented in the literature on EV-mediated interactions between MSCs and tumors.